Doping effect of malic acid on the grown lithium sulfate monohydrate oxalate single crystals. (29th July 2018) - Sumangali, E. Glitta; Joshi, Girish M.
Abstract: Single crystals of semi organic pure and malic acid doped lithium sulfate monohydrate oxalate have been grown at ambient temperature by slow evaporation method using aqueous solution. The single crystal and powder X-ray diffraction techniques were employed to determine the crystallinity, crystal structure and lattice parameters of the grown crystals. The UV-Visible Spectral study revealed the improved transparency in the visible region of the doped crystal ascertaining the inclusion of malic acid. Fourier transform infrared spectral analysis was employed to identify the presence of a various functional groups. The Energy Dispersive X ray analysis was used to find the chemical compositions of the grown crystals. It proved the presence of dopant in the grown crystal. The Vickers microhardness test confirmed the higher hardness value of the crystals.